Resiliensi dan Stres Kerja pada Karyawan yang Bekerja di Masa Pandemi Covid-19 - Agatha Trisia Veronica Tampombebu; Sutarto Wijono (Kuras Institute, 2022)
This study aims to determine the relationship between resilience and work stress on employees at PT.X who work during the covid-19 pandemic. Participants in this study were employees who served as supervisors at PT.X with a total population of 37 participants. The method used in this study is a quantitative approach, with a non-probability sampling technique, namely a saturated sampling technique by taking the entire population of 37 participants. Measurement of resilience uses the Connor-Davidson Resilience Scale (CD-RISC) with a cronbach alpha of 0.917, while to measure work stress uses the work stress scale of Robbins & Judge (2013) with a cronbach alpha of 0.861. The scale is distributed in the form of a questionnaire, with data analysis using IBM SPSS Statistics version 21 and correlation test using Karl Pearson's Product Moment. the results of data analysis obtained a correlation coefficient r = - 0.380 with a sign value = 0.010 (p <0.05), indicating that the results obtained were significant negative, which means there is a significant negative correlation between resilience and work stress. The higher the resilience, the lower the work stress, and vice versa.